The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/cells12222609
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibitor Rapalink-1 Prevents Ethanol-Induced Senescence in Endothelial Cells

Huakang Zhou,
Xuanchen Li,
Majeed Rana
et al.

Abstract: The cardiovascular risk factors, including smoking, ethanol, and oxidative stress, can induce cellular senescence. The senescent cells increase the expression and release of pro-inflammatory molecules and matrix metalloproteinase (MMPs). These pro-inflammatory molecules and MMPs promote the infiltration and accumulation of inflammatory cells in the vascular tissue, exacerbating vascular tissue inflammation. MMPs damage vascular tissue by degenerating the extracellular matrix. Consequently, these cellular and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… 65 Therefore, in addition to shear stress, the proinflammatory and oxidative effect of angiotensin II and increased salt intake should be considered while investigating anti‐inflammatory interventions in a mouse model of the IAs. Moreover, angiotensin II and high salt promote endothelial dysfunction, 67 , 68 which consequently increases the expression of proinflammatory molecules and MMPs 69 , 70 , 71 , 72 that are known to contribute to IA pathophysiology 5 , 55 , 58 ; therefore, while using an animal model using angiotensin II or deoxycorticosterone to study endothelial dysfunction in IAs formation, the direct effect of angiotensin II and high salt on endothelial cells should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Therefore, in addition to shear stress, the proinflammatory and oxidative effect of angiotensin II and increased salt intake should be considered while investigating anti‐inflammatory interventions in a mouse model of the IAs. Moreover, angiotensin II and high salt promote endothelial dysfunction, 67 , 68 which consequently increases the expression of proinflammatory molecules and MMPs 69 , 70 , 71 , 72 that are known to contribute to IA pathophysiology 5 , 55 , 58 ; therefore, while using an animal model using angiotensin II or deoxycorticosterone to study endothelial dysfunction in IAs formation, the direct effect of angiotensin II and high salt on endothelial cells should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). The expression of SASP factor is increased in endothelial cells as a consequence of stress induced premature senescence [ 26 , 27 , 38 , 39 ]. Colchicine mitigated the mRNA expression of the SASP factors induced by tobacco smoke condensate in endothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). It has already been reported that DNA damage, oxidative stress, and ethanol can activate these pathways [ 21 , 26 , 27 , 38 , 39 ]. Activation of these pathways has been linked to cellular senescence, and inhibiting these pathways could block cellular senescence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%